2020
DOI: 10.3390/molecules25040929
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of COD Fraction Forms and Molecules Size on Hydrolysis Process Developed by Comparative OUR Studies in Activated Sludge Modelling

Abstract: The activated sludge models (ASMs) commonly used by the International Water Association (IWA) task group are based on chemical oxygen demand (COD) fractionations. However, the proper evaluation of COD fractions, which is crucial for modelling and especially oxygen uptake rate (OUR) predictions, is still under debate. The biodegradation of particulate COD is initiated by the hydrolysis process, which is an integral part of an ASM. This concept has remained in use for over 30 years. The aim of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…For both the nitrogenous and carbonous quality parameters, the obtained simulated values of the Snh for the plant data follow the GPS-X default value of 0.9. The ASM1 model adopted in this study considers both XND and XS as transformed into SS and SND, respectively, via hydrolysis [5,45], which is evident from the presented results. The ASPs are common, operational under carbon-limited conditions with COD/BOD5 ratio as an acceptable index for evaluating the biological treatability efficacy of municipal wastewater [38,44,47].…”
Section: Influence Of Influent Wastewater Cod Fractioning and Nitrogementioning
confidence: 93%
See 3 more Smart Citations
“…For both the nitrogenous and carbonous quality parameters, the obtained simulated values of the Snh for the plant data follow the GPS-X default value of 0.9. The ASM1 model adopted in this study considers both XND and XS as transformed into SS and SND, respectively, via hydrolysis [5,45], which is evident from the presented results. The ASPs are common, operational under carbon-limited conditions with COD/BOD5 ratio as an acceptable index for evaluating the biological treatability efficacy of municipal wastewater [38,44,47].…”
Section: Influence Of Influent Wastewater Cod Fractioning and Nitrogementioning
confidence: 93%
“…The tCOD in wastewater organic matter is divided into biodegradable and non-biodegradable components, Equation (4), with a relative proportion of these components known to influence the efficacy of biological treatment processes [11,12,38,44,45]. However, in biological processes such as ASP, further subdivisions do exist, including active biomass (X BH and X BA discussed under Section 3.3.8) that forms part of the tCOD [12,24,44,45].…”
Section: Influence Of Influent Wastewater Cod Fractioning and Nitrogementioning
confidence: 99%
See 2 more Smart Citations
“…In order to deal with phosphorus removal, biological (processes of phosphorus-accumulating organisms) and chemical (chemical precipitation of phosphates) processes were included in the model. However, after the publication of ASM2, it has been shown that a fraction of phosphorus-accumulating organisms (PAOs) can denitrify (Gernaey et al, 2004;Drewnowski et al, 2020). Therefore, in 1999, ASM2 International Journal of Environment andGeoinformatics 8(1):001-018 (2021) was expanded into the ASM2d which considers the denitrification caused by PAOs (Makinia et al, 2020).…”
Section: Introductionmentioning
confidence: 99%